Comparison of Admission ICH Score Between Primary Hypertensive and Secondary Intracerebral Hemorrhage due to Vascular Etiologies - Dewi Setyaning Bastiana; Achmad Firdaus Sani; Sita Setyowatie; Jovian Philip Swatan; Atilla Özcan Özdemir (Journal of Neurointervention and Stroke, 2026)
Highlight: Primary hypertensive ICH is the most common etiology of ICH in our study Primary ICH has a higher admission ICH score than secondary ICH Elevated admission BP is associated with higher ICH severity ABSTRACT Introduction: Intracerebral hemorrhage (ICH) is a stroke subtype associated with a high case-fatality rate despite being less prevalent than ischemic stroke. Spontaneous ICH is broadly classified into primary and secondary etiologies, yet clinical evidence remains conflicting regarding which group presents with greater initial severity. Objective: To compare admission ICH scores between primary hypertensive and secondary vascular ICH. Method: This retrospective study included adults with non-traumatic ICH who presented within 48 hours at an Indonesian stroke center. All patients underwent cross-sectional imaging and angiography; those with coagulopathy, anticoagulant use, or recurrent strokes were excluded. The primary outcome was clinical severity, dichotomized using an admission ICH score of ≥3 versus <3. Bivariate tests and multivariate logistic regression were used to identify independent predictors of high severity. Result: Of the 306 patients analyzed, 267 (87.25%) were diagnosed with primary ICH and 39 (12.75%) with secondary ICH. Secondary etiologies included ruptured arteriovenous malformations (n=21), intracranial aneurysms (n=16), and dural arteriovenous fistula (n=2). Patients with primary ICH were significantly older and exhibited higher admission blood pressure and more frequent infratentorial hematoma locations. Conversely, those in the secondary ICH group were typically younger and more likely to present with seizures or concomitant subarachnoid hemorrhage. Primary ICH was independently associated with greater clinical severity, as indicated by an admission ICH score of ≥3 (29.59% vs 7.69%; aOR 5.04, 95% CI 1.51–16.86, p=0.009). Conclusion: Primary ICH exhibits higher admission severity than secondary ICH. Prospective research is required to evaluate long-term functional outcomes.